Laws, aid, and change: The effect of gender-mainstreamed aid on legal provisions shaping women's economic opportunities - Bedassa Tadesse; Elias Kedir Shukralla; Bichaka Fayissa (Economies, 2025)
This study examines the relationship between gender-related aid and legal frameworks governing women's economic opportunities. Using data from 116 countries (2009-2022), we analyze how significant (SGRA) and principal (PGRA) gender-related aid influence the Women, Business, and Law (WBL) Index, which measures women's access to employment, credit, and entrepreneurship. Results from fixed-effects models show that SGRA consistently improves WBL Index components, while PGRA significantly impacts marriage, parenthood, and mobility regulations, with modest effects on workplace and entrepreneurship measures. PGRA substantially affects marriage, parenthood, and mobility regulations while demonstrating more modest impacts on workplace conditions and entrepreneurship measures. These observations underscore the complexity of addressing gender inequality and the necessity of targeted, multifaceted approaches to overcome legal restrictions, entrenched social norms, and economic barriers. The research offers valuable insights for policymakers and donors on the transformative potential of gender-mainstreamed aid initiatives in fostering a more equitable world.
Keywords: F35; J16; K38; O19; P48; 330; legal reforms; gender-mainstreamed aid; women; economic opportunities; change